2008
DOI: 10.1088/0004-637x/690/1/1018
|View full text |Cite
|
Sign up to set email alerts
|

MULTIWAVELENGTH OBSERVATIONS OF 3C 454.3. I. THEAGILE2007 NOVEMBER CAMPAIGN ON THE “CRAZY DIAMOND

Abstract: We report on a multiwavelength observation of the blazar 3C 454.3 (which we dubbed crazy diamond) carried out on November 2007 by means of the astrophysical satellites AGILE, INTEGRAL, Swift, the WEBT Consortium, and the optical-NIR telescope REM. Thanks to the wide field of view (FoV) of the AGILE satellite and its prompt alert dissemination to other observatories, we obtained a long (three weeks), almost continuous γ-ray coverage of the blazar 3C 454.3 across fourteen decades of energy. This broad-band monit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 51 publications
6
39
0
Order By: Relevance
“…The data from AGILE and Fermi were separately used to study the correlations between flux variations in optical and γ-rays. All results agreed that the time lag of γ-ray flux variations after the optical 1 http://www.oato.inaf.it/blazars/webt/ 2 http://agile.iasf-roma.inaf.it/ 3 http://fermi.gsfc.nasa.gov/ ones is less than one day (Vercellone et al 2009;Donnarumma et al 2009;Bonning et al 2009;Vercellone et al 2010). Finke & Dermer (2010) discuss the spectral break at ∼2.4 GeV shown by Fermi data in August 2008 suggesting that it results from the combination of Compton-scattered disc and BLR radiations.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…The data from AGILE and Fermi were separately used to study the correlations between flux variations in optical and γ-rays. All results agreed that the time lag of γ-ray flux variations after the optical 1 http://www.oato.inaf.it/blazars/webt/ 2 http://agile.iasf-roma.inaf.it/ 3 http://fermi.gsfc.nasa.gov/ ones is less than one day (Vercellone et al 2009;Donnarumma et al 2009;Bonning et al 2009;Vercellone et al 2010). Finke & Dermer (2010) discuss the spectral break at ∼2.4 GeV shown by Fermi data in August 2008 suggesting that it results from the combination of Compton-scattered disc and BLR radiations.…”
Section: Introductionsupporting
confidence: 71%
“…The results of these observations were published in Vercellone et al (2008), Raiteri et al (2008a,b), Vercellone et al (2009), Donnarumma et al (2009), Villata et al (2009a), and Vercellone et al (2010). Rotations of the optical polarisation vector both clockwise and counterclockwise were detected by Sasada et al (2010).…”
Section: Introductionmentioning
confidence: 74%
“…For instance, an upper limit lag of about 1 day between IR/optical and gamma-ray fluxes has been reported (Bonning et al 2009;Vercellone et al 2010), while a possible delay between the gamma-ray and the optical is constrained to within 12 h (Donnarumma et al 2009;Vercellone et al 2009). …”
Section: Correlated Variabilitymentioning
confidence: 99%
“…However, recent multiwavelength studies on a number of blazars, which included observations by the γ-ray satellite AGILE, have shown that multiple SSC and/or EC components are necessary to explain the observed high-energy fluxes (see e.g. Chen et al 2008;Pucella et al 2008;Vercellone et al 2009;D'Ammando et al 2009;Donnarumma et al 2009a).…”
Section: Introductionmentioning
confidence: 99%